Low‐cost power gating solution to increase energy efficiency optimising duty cycling in wireless sensor nodes with power‐hungry sensors. (1st February 2019) - Pinzi, Michele; Pozzebon, Alessandro
Abstract : In this study, a solution focusing on energy efficiency of wireless sensor nodes is presented. Energy dissipation is a key factor affecting the usability of wireless sensor networks (WSNs) in that, in worst cases, in systems without electric mains, the life of a sensor node battery may last even only a few hours. The proposed solution is characterised by very low costs thanks to the use of a small number of electronic components: it allows the optimisation of duty cycling (i.e. the ratio between activity and inactivity periods of sensor nodes) by power gating the node (i.e. turning the whole circuitry off). In particular, this solution is useful for applications that use active power‐hungry sensors that are sampled regularly 10 to 1000 times a day. The described power control logic system is able to optimise the duty cycling, notably reducing the power consumption during idle periods, thus increasing the battery life at best up to 100–200 times: this means that the autonomous operation time of a WSN can increase from a few days to several months or even to some years according to the required sampling rate.